2014
DOI: 10.5423/rpd.2014.20.1.001
|View full text |Cite
|
Sign up to set email alerts
|

Update on the Effects of Sound Wave on Plants

Abstract: Plant growth is considered the sum of cell proliferation and subsequent elongation of the cells. The continuous proliferation and elongation of plant cells are vital to the production of new organs, which have a significant impact on overall plant growth. Accordingly, the relationship between environmental stimuli, such as temperature, light, wind, and sound waves to plant growth is of great interest in studies of plant development. Sound waves can have negative or positive effects on plant growth. In this rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 59 publications
0
29
0
Order By: Relevance
“…Therefore, studies involving the use of sound as a trigger have been recognized as fringe science. However, recent findings using cutting-edge technology, quality control for hertz and decibel levels, and the integration of big data have helped change the viewpoint about this field as it has entered the realm of generally accepted science ( Gagliano et al, 2012 ; Chowdhury et al, 2014 ; Mishra et al, 2016 ). We now believe that plants can indeed benefit from sound through their mechanosensory machinery.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, studies involving the use of sound as a trigger have been recognized as fringe science. However, recent findings using cutting-edge technology, quality control for hertz and decibel levels, and the integration of big data have helped change the viewpoint about this field as it has entered the realm of generally accepted science ( Gagliano et al, 2012 ; Chowdhury et al, 2014 ; Mishra et al, 2016 ). We now believe that plants can indeed benefit from sound through their mechanosensory machinery.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, irradiation with a frequency of 0.1-2 kHz, loudness of 100 dB increases the permeability of membranes, improves the activity of protective enzymes and cell division rate. The biomass growth raises by 6-30 % depending on the frequency applied [7,8]. In [8,9], it is found that both sound and ultrasound irradiation increase the active transport rate in plant cells as a result of increased activity of membrane Н + -ATPase under the high content of Ca 2+ ions in the cytoplasm.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Sound spectrum irradiation also has a stimulating effect on the cells of higher plants [7][8][9]. Thus, irradiation with a frequency of 0.1-2 kHz, loudness of 100 dB increases the permeability of membranes, improves the activity of protective enzymes and cell division rate.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Many studies proved that acoustic waves are an external factor that has a great impact on the biological index of plants and can either promote or suppress growth [15]. On the other hand, only a few studies were made regarding the application of acoustic waves in the storage of the perishable crops.…”
Section: Introductionmentioning
confidence: 99%